Altruistic values among students of Nursing, Midwifery, Physiotherapy, and Health Psychology: a cross-sectional study - J. Kraja; E. Fresku; L. Xhakollari (Medičnì Perspektivi)
Aim – to study the altruistic values of o group of nursing, midwifery, and physiotherapy students, and how these values evolved throughout academic years and across study programs. The study used a descriptive correlational design. The data were collected from students in the bachelor’s degree programs in nursing, midwifery, and physiotherapy, and in the master's degree program in health psychology (students in this program have completed bachelor’s degrees in nursing, midwifery, or physiotherapy). The Faculty of Natural Sciences at the University of Shkodra “Luigi Gurakuqi”, Albania offers bachelor’s degree programs in nursing, midwifery, physiotherapy and a professional master's degree in health psychology. During the academic year 2022-2023, the number of active students was 756. A total of 457 students participated in this study: 175 from the nursing program, 130 from the midwifery program, 107 from the physiotherapy program, and 45 from master program. Data were collected from December 1, 2022, through January 31, 2023, with an online questionnaire. Two tools were used in this study: a demographic questionnaire and the Altruism Scale used by Űmmet and colleagues. The mean score on the Altruism Scale was 2.9±0.78. A one-way ANOVA revealed that there was a difference in mean altruism score between at least two groups (F (3, 452) = [3.232], p=0.02). Tukey’s HSD Test for multiple comparisons found out that the mean value of altruism was different between the bachelor students in nursing and bachelor students in physiotherapy (p=0.011, 95% CI = [0.0498, 0.5448]). Compared to others, bachelor students in nursing had higher level of altruism and bachelor students in physiotherapy had lower level of altruism. Conclusions: The results showed that it is precisely the feeling of altruism that people have, which made them choose nursing as a profession. Since altruism is so important for the nursing profession, topics related to altruism should be included in nursing curricula.